Analysis of the Effectiveness and Efficiency of Billboard Tax Collection and its Contribution to the Original Revenue of Makassar City - Muhammad Fardhan Dinarto; Baso Amang; Muhammad Nur (Universitas Muhammadiyah Makassar, 2024)
This research aims to increase the prosperity and welfare of the people. Tax collection is a manifestation of community participation in the context of routine government financing and development in a mutual cooperation, so that taxes have a strategic position in state revenue. The population in this study is a company of the Makassar City Regional Revenue Office, using premier data on companies. Data analysis techniques carried out are comparative descriptive methods by finding and collecting data, analyzing and processing data, researching suitability, then from the results of data processing, namely by drawing conclusions. Based on the analysis that has been carried out that the effectiveness of billboard revenue at the Makassar City Regional Revenue Office in 2018 - 2022 shows very effective results because the value obtained is in accordance with the criteria, which is more than 100% and the level of efficiency of collecting billboard tax in the Makassar city area from 2018 to 2022 is in the very efficient category and the contribution of billboard tax revenue during 2018-2022 is very less, The highest contribution was in 2022 while the largest decline occurred in 2018.